BRANDING PRIBADI GURU MI SEBAGAI MODAL EDUPRENEURSHIP DI ERA MEDIA SOSIAL - Alya Nadiastuti; Anindia Ameliani Fernanda; Widi Jauza Labilla; Ulva Milda Tisana; Nur Khasanah; Ferida Rahmawati (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
This paper explores how personal branding can serve as an asset for Madrasah Ibtidaiyah teachers who want to develop edupreneurship activities on social media. The problem stems from teachers’ need to position themselves professionally while creating economic opportunities through digital educational content and services, yet focused studies on the MI context remain scarce. The aims are to outline practical personal branding strategies for MI teachers, assess their benefits for educational ventures, and identify realistic implementation steps. The method is a literature review drawing on books, articles, and policy reports to synthesize best practices in content creation, reputation management, audience engagement, and service monetization. Key findings include: the necessity of grounding identity in clear pedagogical values and competencies; using social platforms to distribute learning materials and build professional networks; maintaining consistent communication to earn trust from parents and stakeholders; and diversifying offerings—such as digital modules, short online classes, or consulting—as revenue streams. In conclusion, well-planned personal branding rooted in professional ethics offers MI teachers viable paths to become edupreneurs without compromising their educational role, and it calls for targeted training and supportive policies to enable this shift.